Regional and multilateral liberalization of service markets : complements or substitutes? - HOEKMAN, Bernard (1994)
Compares the major services-related regional agreements involving OECD countries, viz. EC, FTA, NAFTA, CER, in an attempt to determine the extent to which they go beyond the General Agreement on Trade in Services (GATS) in terms of effective liberalization of service markets. Focuses on whether regional agreements and the multilateral process are complementary or substitute paths liberalizing services markets. Suggests that regional and multilateral agreements display a fairly strong degree of complementarity.